Characteristics of the oil of different varieties of avocado grown in Brazil and a new methodology for extra-virgin avocado oil extraction - Alnasan, Zaenab (2019)
Tese (doutorado)—Universidade de Brasília, Faculdade de Agronomia e Medicina Veterinária, Programa de Pós-Graduação em Agronomia, 2019.